A Head-to-Head Comparison of Augmented Wealth in Germany and the United States - Timm Bönke; Carsten Schröder; Markus Grabka; Edward Wolff (ZBW - Leibniz-Informationszentrum Wirtschaft, 2018)
We provide levels of, compositions of, and inequalities in household augmented wealth – defined as the sum of net worth and pension wealth – for two countries: the United States and Germany. Pension wealth makes up a considerable portion of household wealth: about 48% in the United States and 61%in Germany. The higher share in Germany narrows the wealth gap between the two countries: While average net worth in the United States (US337,000 in 2013) is about 1.8 times higher than in Germany, augmented wealth (US651,000) is only 1.4 times higher. Further, the inclusion of pension wealth in household wealth reduces the Gini coefficient from 0.892 to 0.701 in the United States and from 0.765 to 0.511 in Germany.
Keywords: D31; H55; J32; 330